PENGARUH PENDAMPINGAN ORANG TUA PADA PEMBELAJARAN DARING TERHADAP KECERDASAN EMOSIONAL - Ghesya Athira Hasna’ul Fauzyah; Luthfi Hamdani Maula; Iis Nurasiah (Jurnal Pendidikan Dasar, 2020)
The study consisted of two variables, namely the parent's companion variable as independent variable (X) and the emotional intelligence variable as dependent variable (Y). This study aims to determine the description and describes the influence of parental mentoring on online learning to the emotional intelligence of elementary school students during the Covid 19 pandemic. This study uses a type of quantitative survey research methodology. The Data is obtained by using questionnaire that is distributed to respondents were 58 students and parents of class V at SDI Al-Azhar 7 Kota Sukabumi. The validity test is carried out using the Product Moment formula and the Realibility test using the Alpha Cronbarch Approach. The distribution of these questionnaires are conducted online through Google forms. Data analysis techniques use a correlation coefesien and a simple linier regression formula with the help of SPSS of the first hypothesis test () or = 0.637 with the significance of 0.000 compared to α = 5% then the 0.000 of < 0.05 then rejected accepted. And a regression equation on the influence of parental accompaniment to emotional intelligence i.e. Y = 68,854 + 0.681 X. So this indicates that each addition of one value accompaniment of parents will add value to emotional intelligence hence the variable parental mentoring of the variable emotional intelligence has influence. Keywords: parent's companion, online learning, emotional intelligence